Commiphora mukul and Quercetin Loaded Liposphere Gel: Potential Treatment for Psoriasis - Mestry, Madhura; Rane, Meenal; Bajaj, Amrita (Indian Journal of Pharmaceutical Education and Research, 2020)
Background: Psoriasis is a chronic autoimmune skin disorder characterized by thick skin patches, which are typically red, scaly and itchy. Topical drug delivery is backbone in mild and moderate psoriasis as well as useful complementary therapy to systemic therapy in severe conditions. Aim: The attempt was made to formulate, optimized and evaluate novel liposhpere based drug delivery system containing anti-psoriatic herbal drug such as Commiphora mukul and Quercetin for treatment of psoriasis. Materials and Methods: Liposphere were prepared separately for both the drugs by using Precirol ATO 5, Phosphotidylcholine, poloxamer 338. Physicochemical characteristics of the liposphere such as, particle size, drug encapsulation efficiency were determined. Also, drug release and in vitro skin permeability were evaluated using Franz diffusion cells. Results: The results showed that the maximum encapsulation efficiency was 83% and 81.77% for Commiphora mukul and Quercetin loaded liposphere respectively. In vitro study was observed that F1 liposphere gel attributed 89.28 % release in 1440 min (24 hr) and F2 conventional cream batch attributed 80.24% release in 540 min (9 hr). As per the result it was observed that liposphere gel gives more sustained release as compared to conventional cream. The results substantiate that liposphere gel containing combination of Commiphora mukul and Quercetin can be an efficacious for the treatment of psoriasis.
Keywords: Commiphora mukul; Combination therapy; Imiquimod induced psoriasis; model; Lipospheres; Psoriasis; Quercetin